EVALUATION OF THERAPEUTIC PROTOCOLS FOR INDUCTION OF WHELPING IN BITCHES - REDDY, K.RAM CHANDRA; RAO, K SADASIVA; RAJU, K G S; RAGHAVENDER, K B P; REDDY, A GOPAL (The Indian Journal of Animal Reproduction, 2023)
A total of 29 full term pregnant bitches not showing signs of whelping were utilized for induction. The mean duration of time interval from starting of treatment to begini· :ng of whelping, duration of whelping and inter pup intervals (in hours) were 34.46 ± 4. 70, 8.17 ± 1.52 and 3.20 ± 1.04 respectively in cloprostenol group, 40.48 ± 6.4 7, 4.22 ± 0.80 and 1.13 ± 0.18 respectively in dinoprostone plus cloprostenol group and 26.98 ± 4.51 , 5.9 ± 1.43 and 1.02 ± 0.16 in mifepristone plus cloprostenol group. Duration of whelping was 8.34 ± 0.40 and inter pup interval was 1.31 ± 0.13 hrs in the control group. Whelping was induced successfully in three treatment groups, but dinoprostone plus cloprostenol was a better protocol because it required less obstetrical assistance, shorter duration of whelping. Followed by mifepristone plus cloprostenol group and cloprostenol group.